2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2011
DOI: 10.1109/icassp.2011.5947108
|View full text |Cite
|
Sign up to set email alerts
|

Closed-form parameterization of the Pareto boundary for the two-user MISO interference channel

Abstract: In this paper, we study an achievable rate region of the two-user multiple-input single-output (MISO) interference channel. We find the transmit beamforming vectors that achieve Pareto-optimal points. We do so, by deriving a sufficient condition for Pareto optimality. Given the beamforming vector of one transmitter, this condition enables us to determine the beamforming vector of the other transmitter that forms a Pareto-optimal pair. The latter can be done in closed form by solving a cubic equation. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…To complete the picture, note that there are special cases when the Pareto boundary can be characterized in a necessary and sufficient manner without the need for numerically solving an optimization problem for each point. Example 3.1 showed that this is possible for the two-user interference channel with per-transmitter power constraints [149,181] and Corollary 3.7 showed it for L =1.…”
Section: Necessary and Sufficient Pareto Boundary Parametrizationmentioning
confidence: 99%
See 2 more Smart Citations
“…To complete the picture, note that there are special cases when the Pareto boundary can be characterized in a necessary and sufficient manner without the need for numerically solving an optimization problem for each point. Example 3.1 showed that this is possible for the two-user interference channel with per-transmitter power constraints [149,181] and Corollary 3.7 showed it for L =1.…”
Section: Necessary and Sufficient Pareto Boundary Parametrizationmentioning
confidence: 99%
“…Example 2.6 (ǫ-Constraint Optimization). The ǫ-constraint optimization represents maximizing the performance of MS k , while guaranteeing that g i ≥ ǫ i for all i [38,98,123,149,278,292,293]. This problem is solved by Theorem 2.10 using r k (τ )=τ + ǫ k and r i (τ )=ǫ i .…”
Section: Quasi-fixed Quality-of-service Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The -constraint optimization represents maximizing the performance of MS k , while guaranteeing that g i ≥ i for all i [38,98,123,149,278,292,293]. This problem is solved by Theorem 2.10 using r k (τ ) = τ + k and r i (τ ) = i .…”
Section: Example 26 ( -Constraint Optimization)mentioning
confidence: 99%
“…In [3] we computed an arbitrary point on the boundary via a sequence of second-order cone (SOC) programs. In [4], we gave a closed-form parameterization of the beamforming vectors that yield PO rate points. The methods for finding R dn , R nd , and R dd devised in the sequel are novel.…”
Section: Efficient Computation Of the Pareto Boundarymentioning
confidence: 99%